2016
DOI: 10.1186/s13049-016-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital treatment with continuous positive airway pressure in patients with acute respiratory failure: a regional observational study

Abstract: BackgroundPatients with acute respiratory failure are at risk of deterioration during prehospital transport. Ventilatory support with continuous positive airway pressure (CPAP) can be initiated in the prehospital setting. The objective of the study is to evaluate adherence to treatment and effectiveness of CPAP as an addition to standard care.MethodsIn North Denmark Region, patients with acute respiratory failure, whom paramedics assessed as suffering from acute cardiopulmonary oedema, acute exacerbation of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
6
0
6
Order By: Relevance
“…Ambulance staff are trained to perform advanced airway support, frequently using devices and techniques in the prehospital setting that were formerly used exclusively in hospitals, such as invasive mechanical ventilation (through orotracheal intubation and video laryngoscopes) and the increasingly used noninvasive mechanical ventilation. 23 , 24 Patients who require advanced procedures of airway management should be accompanied by continuous monitoring, using Sp o 2 as standard to monitor oxygenation. 25 In addition, capnography (end-tidal C o 2 ) can be used to assess ventilation, 5 , 6 which is also useful for predicting mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulance staff are trained to perform advanced airway support, frequently using devices and techniques in the prehospital setting that were formerly used exclusively in hospitals, such as invasive mechanical ventilation (through orotracheal intubation and video laryngoscopes) and the increasingly used noninvasive mechanical ventilation. 23 , 24 Patients who require advanced procedures of airway management should be accompanied by continuous monitoring, using Sp o 2 as standard to monitor oxygenation. 25 In addition, capnography (end-tidal C o 2 ) can be used to assess ventilation, 5 , 6 which is also useful for predicting mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This requires advanced knowledge from the PENs who is caring for patients with dyspnoea, as abnormal vital parameters may be a sign of a number of different serious conditions; both cardiogenic, pulmonary and other aetiologies of acute respiratory failure. This highlights the importance of early recognition of the patients condition and directed treatment already at an early stage by EMS, as it might be crucial for the final outcome [ 33 35 ]. It has previously been reported that acute ill patients (including those with dyspnoea) admitted thorough ED [ 36 ] with abnormal vital parameters, have an increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The application of pre-hospital CPAP for the emergency treatment of acute respiratory failure (ARF) is increasingly used by emergency medical services. 1 In non-traumatic ARF, prehospital application CPAP via a tight-fitting mask reduces ventilatory frequency and the need for subsequent intubation. 2e4 Additionally, porcine data suggest the potential for decreased mortality, decreased pulmonary oedema, and increased arterial oxygen saturation after toxic lung injury when ambient-air CPAP is administered shortly after injury.…”
Section: Editor's Key Pointsmentioning
confidence: 99%